Ester - eine Gewaltgeschichte: die Gewaltdarstellungen in der hebräischen und griechischen Esterüberlieferung - Bezold, Helge (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2022)
The Book of Esther tells the story of a plot to exterminate the Persian Jews and their great struggle against their enemies. This study locates these portrayals of violence in the Hellenistic epoch, in the Hasmonean period (second century BCE). It compares the Hebrew text with the two Greek Books of Esther, thus providing insights into a dynamic discourse of violence in Hellenistic and Roman literature